Renal disease associated with myeloproliferative neoplasms and myelodysplastic syndrome/myeloproliferative neoplasms - Büttner-Herold, Maike; Sticht, Carsten; Wiech, Thorsten; Porubsky, Stefan (Histopathology, 2020)
Aims: Renal changes in patients with myeloproliferative neoplasms (MPNs) or myelodysplastic syndrome (MDS)/MPNs have been addressed by few, respectively no, reports. The aim of this study was to focus on a systematic evaluation of renal biopsies in patients with MPNs or MDS/MPNs. Methods and results: The cohort comprised 29 patients (23 men) aged 67 ± 11 years (mean ± standard deviation), diagnosed with chronic myeloid leukaemia (n = 5), polycythaemia vera (n = 9), primary myelofibrosis (n = 5), essential thrombocythaemia (n = 2), or chronic myelomonocytic leukaemia (n = 4), as well as MPNs or MDS/MPNs not otherwise specified (n = 4). Patients manifested with proteinuria (93%), partially in the nephrotic range (46%), haematuria (72%), and impaired kidney function (93%). The most prominent histological findings included double-contoured glomerular basement membranes (71%), acute endothelial damage (68%), intracapillary platelet aggregation (62%), mesangiolysis (21%), thrombotic microangiopathy (24%), segmental glomerulosclerosis (66%), mesangial hypercellularity and sclerosis, extramedullary haematopoiesis (17%), and also IgA nephropathy (21%) and glomerulonephritis (GN) with features of infection-related GN (21%). MPN and MDS/MPN patients showed significantly more chronic changes than age-matched and sex-matched controls, including global and segmental glomerulosclerosis, mesangial sclerosis, and hypercellularity, whereas the extent of arteriosclerosis was comparable. Conclusions: MPN and MDS/MPN patients show glomerular scarring that exceeds age-related phenomena. Ongoing endothelial damage, growth factors released by platelets and deposition of immune complexes are probably the causative mechanisms. Early recognition of renal failure heralded by proteinuria and haematuria, and consequent control of risk factors for kidney failure, should be recommended for MPN and MDS/MPN patients.
CRIS-Team Scopus Importer:2020-12-25
Keywords: endothelium; glomerulopathy; myelodysplastic syndrome/myeloproliferative neoplasms; myeloproliferative neoplasms; thrombotic microangiopathy